Letter to Miss P Shirley - Anti-Partition League, APL (1939)
Typescript letter from the Honorary Assistant Secretary of the Anti-Partition of Ireland League thanking Miss Shirley for her letter and accepting her invitation to speak to League of Youth branches. Dated 7 March 1939.